APLIKASI TEKNOLOGI SISTEM INFORMASI GEOGRAFIS (SIG) UNTUK HANALISIS POTENSI WILAYAH PESISIR GUNA PENGEMBANGAN PARIWISATA DI KABUPATEN REMBANG - Heri Tjahjono; Rahma Hayati; Galuh Sitoresmi (Forum Ilmu Sosial)
Tourism can be a top priority in supporting the development of a region. Coastal tourism is a potential tourist that will contribute significantly to the community’s economy. Rembang District as one of the coastal tourist destination, located on the north coast of Java and has the potential of natural beauty that is very interesting, but less widely known because of lack of development. The government is currently trying to develop a Rembang district coastal tourist areas to be promoted to some areas. Purpose of this study were (1) determine the potential for coastal areas in the Rembang District, (2) determine how far the development of coastal tourism in Rembang District, and (3) Provide guidance on priority areas for the development of coastal tourism in Rembang District. The variables consisted of physical potential, the social potential, and tourism development. The method of data collection using observation, documentation, and interviews. Analysis of data using scoring techniques, grades and descriptive analysis. The results showed that areas that have the potential for the development of coastal tourism in Rembang District in stages from the highest potential and Sub-district Rembang and Sarang, Sub-distric Kragan, and Lasem. The development of tourism in coastal areas in Rembang District is quite diverse among others include beautiful panorama, cultural tourism, pilgrim (religion), culinary, industrial, and commercial all of which have the potential to be marketed. Great potential is less supported the development of tourism, especially accommodation, infrastructure, facilities and services. Based on the potential physical, social, and tourism development that is directed into 3 main priorities Priority I Rembang and Sarang District are prioritized for the development of cultural tourism and pilgrim tour. Priority II Kragan District that no special priority. Priority III Lasem District priority for pilgrim tourism development